Orthogonal Time Frequency Space Modulation Technology - Castillo Rodríguez, Rodrigo Alberto (2021)
This bibliography research gathers together the basics of the Orthogonal Time Frequency Space (OTFS) modulation technology, that will be used in the fifth generation (5G) mobile communications; it has inherent advantages in the face of the Orthogonal Frequency Division Multiplexing (OFDM) modulation technique, used in the fourth generation mobile communication (4G). One of these profits is its skill to transform a channel that randomly fades within the time-frequency space into a stationary, deterministic and non-fading channel between the transmitter and the receiver. In addition, there is the fact that OTFS modulation operates in a domain in which the channel can be characterized in a very compact way; this has significant implications for tackling the channel estimation bottlenecks that affect current multi-antenna systems and can be an implementing key technology for addressing similar problems in future massive MIMO systems. Finally, the main benefit of OTFS modulation is its ability to easily operate in extreme Doppler channels; this is not only useful in high mobility communications, but can also be an enabling technology for mmWave systems, where Doppler effects will be significantly amplified.